The Improvement of Social Skills By Playing Creative Dance (An Action Research in Group A, PAUD Kasih Ibu, Duren Sawit, East Jakarta, in 2018) - Sabila Nur Masturah (STIT Al-Marhalah Al-Ulya Bekasi, 2018)
The objective of this research was to determine the process of implementation of creative dance in increasing child social skills in group A in PAUD Kasih Ibu Duren Sawit, Jakarta Timur. This research is an action research which refers to the model of classroom action research by Kemmis and Mc. Taggart.The subject of this research are children in Group A PAUD Kasih Ibu Duren Sawit, there are 12 children. The steps of this research : 1) Planning, 2) Action,3) Observation, 4) Reflection. This research consist by two cycles, first cycle consist of eight times in actions and the second cycle consists of four times in actions.The analysis of the data used qualitative and quantitative approaches. The analysis of quantitative data used descriptive statistics that compare the results obtained from the first cycle and the second cycle. While the analysis of qualitative data used analyzing daa from the field notes and interviews during the research by steps of data reduction, data display and data verification.The end of this research is the percentage 47,2% to 64,8% to 81,8%. The findings lead to the recommendation to the teacher and parents to use the playing creative dance as the method to increase student’s social skills.